2019
DOI: 10.1515/sjecr-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Effects of N-Acetylcysteine on Cisplatin-Induced Alterations in Exploratory Activity in Elevated Plus Maze Test in Rats

Abstract: The aim of this study was to evaluate the potential beneficial effect of N-acetylcysteine (NAC) on cisplatin-induced alterations in anxiety levels in rats, by means of parameters of the exploratory activity obtained in the elevated plus maze (EPM) test. Animals were divided into four groups: control group, cisplatin group (7.5 mg/kg/weekly of cisplatin), N-acetylcysteine group (500 mg/kg/weekly of NAC), and cisplatin plus N-acetylcysteine group (7.5 mg/kg/weekly of cisplatin, and 500 mg/kg/weekly of NAC). Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The manifestations of neurotoxicity following cisplatin administration have also been confirmed in animal experimental models. Cisplatin-induced behavioral alterations include cognitive dysfunction [30] and depressive- and anxiety-like behaviors in rats [31, 32]. The results obtained in this study showed a clear anxiogenic effect of cisplatin (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 56%
“…The manifestations of neurotoxicity following cisplatin administration have also been confirmed in animal experimental models. Cisplatin-induced behavioral alterations include cognitive dysfunction [30] and depressive- and anxiety-like behaviors in rats [31, 32]. The results obtained in this study showed a clear anxiogenic effect of cisplatin (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 56%
“…It has been shown that cisplatin administration strongly affects CNS progenitor cells and oligodendrocytes inducing the apoptotic events in hippocampal dentate gyrus and corpus callosum [30]. Only a few studies implicate that several mechanisms of platinum compounds action in CNS, including oxidative damage, inflammation and apoptosis, may be the cause of behavioral alterations manifested as increased anxiety [31], depression [32], as well as cognitive dysfunction [33].…”
Section: Side Effects Of Platinum-based Compounds In Clinical Practicementioning
confidence: 99%